Sistem Presidensial Indonesia dan Syar'iyyah: Relevansi Prinsip Syūrā, Keadilan, dan Akuntabilitas dalam Pemerintahan Demokratis - Said Almuqarrom (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The Indonesian constitutional system adopts a presidential model that has undergone significant transformation following the amendments to the 1945 Constitution. While the constitutional reforms strengthened democratic institutions and the separation of powers, various governance challenges remain, including political oligarchy, weak public accountability, transactional politics, and declining public trust in political institutions. This study aims to analyze the relevance of the principles of syūrā, justice, and accountability in siyāsah syar‘iyyah to the implementation of Indonesia’s presidential system. This research employs normative legal research using statutory, conceptual, historical, and comparative approaches. The findings reveal that Indonesia's presidential system substantively reflects several principles of siyāsah syar‘iyyah, particularly deliberation, public participation, constitutional governance, and public welfare. However, practical implementation still encounters significant challenges in realizing justice, accountability, and public participation. This study proposes a reconstruction of democratic governance based on the integration of constitutional democracy and the values of siyāsah syar‘iyyah through strengthening public accountability, participatory governance, and ethical leadership. The integration of these principles contributes to the development of a democratic governance model that is both constitutionally legitimate and ethically grounded